Effects of hot and cold condition on finishing properties of Mahang Gajah (macaranga gigantae) / Nur Liyana Izzati Rohaffin - Rohaffin, Nur Liyana Izzati (Faculty of Applied Sciences, 2016)
Weather is a state of atmosphere which is consists of hot and cold, dry or wet, calm or stormy, clear or cloudy. The finishing is among the final process before it being sells or exported to customer. The finishing properties of Acid Catalyst on mahang gajah were ascertained. The effect of different layers and condition were determined. Three of finishing properties was chosen to determine the properties of AC lacquer towards layers and condition on boards. This study used American Society for Testing Material (ASTM) for procedures and standard of testing. The result showed that 4 layers have a good performance for all testing but it gives a poor performance for hot condition in cross hatch testing. This is due to the environment humidity